2008
DOI: 10.1186/1471-2105-9-399
|View full text |Cite
|
Sign up to set email alerts
|

Presenting and exploring biological pathways with PathVisio

Abstract: Background: Biological pathways are a useful abstraction of biological concepts, and software tools to deal with pathway diagrams can help biological research. PathVisio is a new visualization tool for biological pathways that mimics the popular GenMAPP tool with a completely new Java implementation that allows better integration with other open source projects. The GenMAPP MAPP file format is replaced by GPML, a new XML file format that provides seamless exchange of graphical pathway information among multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
263
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(268 citation statements)
references
References 20 publications
2
263
0
3
Order By: Relevance
“…Biological Pathways Affected in 22qDS-To gain insight into the metabolic pathways in 22qDS that are different from controls, metabolomics data were analyzed by using PathVisio software (Table 3) and filtered by the false discovery rate p value Յ0.05 (28). This analysis revealed that solute-mediated transmembrane transport of small molecules was overrepresented in 22qDS.…”
Section: Resultsmentioning
confidence: 99%
“…Biological Pathways Affected in 22qDS-To gain insight into the metabolic pathways in 22qDS that are different from controls, metabolomics data were analyzed by using PathVisio software (Table 3) and filtered by the false discovery rate p value Յ0.05 (28). This analysis revealed that solute-mediated transmembrane transport of small molecules was overrepresented in 22qDS.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these confident set of reactions, we developed the pathway map using PathVisio software (van Iersel et al 2008). The topological arrangement of the molecules in the map was based on the information obtained from, i) inhibitor-based assays; ii) mutation-based assays; iii) knockout studies; iv) canonical pathways; and v) review articles.…”
Section: Methodsmentioning
confidence: 99%
“…For comparison with other breast cancer gene expression profiles, a collection of 1,033 breast cancer samples was used as reference dataset (38). Pathway analysis based on the RNASeq data for the two cell populations sorted with CD184 was performed using PathVisio3 (39,40). Significant biological functions were determined using the elim method of …”
Section: Rna Isolation and Rnaseqmentioning
confidence: 99%